2021
DOI: 10.1038/s41598-021-95050-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the structural forces governing the reversibility of the thermal unfolding of the human acidic fibroblast growth factor

Abstract: Human acidic fibroblast growth factor (hFGF1) is an all beta-sheet protein that is involved in the regulation of key cellular processes including cell proliferation and wound healing. hFGF1 is known to aggregate when subjected to thermal unfolding. In this study, we investigate the equilibrium unfolding of hFGF1 using a wide array of biophysical and biochemical techniques. Systematic analyses of the thermal and chemical denaturation data on hFGF1 variants (Q54P, K126N, R136E, K126N/R136E, Q54P/K126N, Q54P/R136… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…To better understand the H-bond and its contributions to the overall stability of each system, an H-bond analysis of natural compounds-Nsp4 complexes were calculated. The hydrogen bonding study indicates that all of the Nsp4-complexes are stable and made bonding with essential catalytic residues [ 49 ]. The overall analysis revealed that each complex was stabilizing after 70 ns indicating better interaction with Nsp4 in terms of stability that is required for its inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the H-bond and its contributions to the overall stability of each system, an H-bond analysis of natural compounds-Nsp4 complexes were calculated. The hydrogen bonding study indicates that all of the Nsp4-complexes are stable and made bonding with essential catalytic residues [ 49 ]. The overall analysis revealed that each complex was stabilizing after 70 ns indicating better interaction with Nsp4 in terms of stability that is required for its inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the thermal stability of FGF-1 is strongly affected by structural changes in and near the heparin binding site. Nullification of charges in the heparin binding pocket by mutagenesis was found to significantly increase the stability of wtFGF-1 (Agrawal et al, 2021), whereas the introduction of a basic residue to extend the heparin binding site (D82R) increased backbone flexibility and reduced biologic activity, in spite of increased affinity for heparin (Davis et al, 2018).…”
Section: Interaction Of Heparin With Chemokines Cytokines and Growth ...mentioning
confidence: 99%